Influence of PPF on leaching and subsidence of Gypseaus soils - Farouk M. Muhauwiss; Ahmed H. salh (Genius Journals, 2022)
Gypsum soils are found in various places, including Iraq. The problems created by gypsum soils are due to the presence of gypsum salts, which dissolve in water and affect the engineering qualities of the soil over time, causing several problems that can finally lead to collapse. This study aims to assess the effect of PPF on the soaked gypseous soil. The tests were carried out on three types of gypseous soil with varying gypsum content and properties, mixed with varying PPF contents (0, 0.25%, 0.5%, and 1%) at 12 mm length. By the compaction results, polypropylene fiber increases the optimum moisture while reducing the maximum dry density.Also, adding (0.5 % PPF) has produced an efficiency percentage of 69.9_74.8% in reducing collapsible potential. For the leaching model test The model test results we found through the leaching process showed that the effect of fibers in stabilizing the soaked gypsum soils was apparent by preserving their engineering structure and preventing deformations and collapses. Whereas untreated soils became brittle and collapsed under the influence of their weight, this reduced the volume by 1795.2 cm3 after 80 days of leaching with water, while the treated soil volume decreased by only 210.5 cm3.%. The current study's findings point to polypropylene fiber improvement as an environmentally friendly technique for enhancing the engineering characteristics of gypseous soil
Keywords: Leaching; Gypseaus Soils; Polypropylene Fiber; Collapse